Launch of Pakistan Journal of Health Sciences - Mehboob, Riffat (Pakistan Journal of Health Sciences, 2020)
Pakistan Journal of Health Sciences (PJHS) is a biannual, peer reviewed, International journal, of Health Sciences. We hereby welcome you to the first issue of PJHS. It will deal with all the articles in medical, health, allied health and related disciplines. Types of studies included will be original articles, review articles, letter to editor, Guest Editorials, systematic reviews and meta-analysis, case studies, case series, commentaries and opinion articles. Health and related disciplines have always been important as they are concerned with the health and well-being of populations. This journal aims to provide a platform to the health professionals, scientists, researchers and students to learn, share knowledge and gain information about the studies of other authors. Looking forward to a welcoming response and scholarly publications from the health professionals across the globe.